The MUSES∗: a prognostic study on 1360 patients with sinonasal cancer undergoing endoscopic surgery-based treatment: ∗MUlti-institutional collaborative Study on Endoscopically treated Sinonasal cancers. (August 2022) - Ferrari, Marco; Mattavelli, Davide; Tomasoni, Michele; Raffetti, Elena; Bossi, Paolo; Schreiber, Alberto; Orlandi, Ester; Taboni, Stefano; Rampinelli, Vittorio; Gualtieri, Tommaso; Turri-Zanoni, Mario; Battaglia, Paolo; et al.
Abstract: Background: Over the last 2 decades, transnasal endoscopic surgery (TES) has become the most frequently employed surgical technique to treat sinonasal malignancies. The rarity and heterogeneity of sinonasal cancers have hampered large non-population-based analyses. Methodology: All patients receiving TES-including treatment between 1995 and 2021 in 5 referral hospitals were included. A prognostic study was performed, and multivariable models were transformed into nomograms. Training and validation sets were based on results from 3 European and 2 non-European centres, respectively. Results: The training and validation set included 940 and 420 patients, respectively. The mean age at surgery, primary-versus-recurrent presentation, histology distribution, type of surgery, T category and type of adjuvant treatment were differently distributed in the training and validation set. In the training set, 5-year overall survival and recurrence-free survival with a 95%-confidence interval were 72.7% (69.5–76.0%) and 66.4% (63.1–69.8%), respectively, significantly varying with histology. At multivariable analyses, age, gender, previous treatment, the extent of resection on the cranial, lateral and posterolateral axes, grade/subtype, T category, nodal status, margin status and adjuvant treatment were all associated with different prognostic outcomes, displaying a heterogeneous significance and effect size according to histology. The internal and external validation of nomograms was satisfactory (optimism-corrected C-index >0.7 and cumulative area under curve >0.7) for all histologies but mucosal melanoma. Conclusions: Outcomes of TES-based treatment of sinonasal cancers vary substantially with histology. This large, non-population-based study provides benchmark data on the prognosis of sinonasal cancers that are deemed suitable for treatment including TES. Highlights: The largest study on sinonasal cancers treated with transnasal endoscopic surgery. Analysis of prognostic factors based on 20-year multidisciplinary experience. Multivariable analysis with internal and external validation of prognostic models. Benchmark data on outcomes of patients affected by rare cancers. Comparison between European, North American, and Asian cohorts of patients.